Factor structure, internal consistency and reliability of the Posttraumatic Stress Disorder Checklist (PCL): an exploratory study - Lima,Eduardo de Paula (2012)
INTRODUCTION: Posttraumatic stress disorder (PTSD) is an anxiety disorder resulting from exposure to traumatic events. The Posttraumatic Stress Disorder Checklist (PCL) is a self-report measure largely used to evaluate the presence of PTSD. OBJECTIVE: To investigate the internal consistency, temporal reliability and factor validity of the Portuguese language version of the PCL used in Brazil. METHODS: A total of 186 participants were recruited. The sample was heterogeneous with regard to occupation, sociodemographic data, mental health history, and exposure to traumatic events. Subjects answered the PCL at two occasions within a 15 days’ interval (range: 5-15 days). RESULTS: Cronbach’s alpha coefficients indicated high internal consistency for the total scale (0.91) and for the theoretical dimensions of the Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV) (0.83, 0.81, and 0.80). Temporal reliability (test-retest) was high and consistent for different cutoffs. Maximum likelihood exploratory factor analysis (EFA) was conducted and oblique rotation (Promax) was applied. The Kaiser-Meyer-Olkin (KMO) index (0.911) and Bartlett’s test of sphericity (χ² = 1,381.34, p < 0.001) indicated that correlation matrices were suitable for factor analysis. The analysis yielded three symptom clusters which accounted for 48.9% of the variance, namely, intrusions, avoidance, and numbing-hyperarousal. CONCLUSION: Our findings provide additional data regarding the psychometric properties of the PCL, including internal consistency, test-retest reliability, and factor validity. Results are discussed in relation to PTSD theoretical models.